Two-dimensional sequence homogeneity testing against mixture alternative - Irina A. Safaryan; Evgueni A. Haroutunian; Arsen V. Manasyan (Изд-во НАН РА)
The behavior of linear rank statistics is investigated on models in which various subsequences of observations follow di®erent statistical distributions. Such data can be interpreted both as models of a ¯nite number distribution mixtures and as dependence models. We apply data set simulation to obtain estimates of average and variance of used rank statistics. The modeled and asymptotic results are enough close.
Keywords: Mathematics